Preconceptional Care: A health service still unknown in Peru - Ormachea-Yabar, Jiene Alexandra (2023)
The preconceptional care is few demanded in Peru, being a service that in many occasions does not have its own office, due to the fact that it is not promoted by the Peruvian health services, being counterproductive for women of reproductive age not knowing the existence of this service to have information and guidance prior to conception.